1985
DOI: 10.1038/bjc.1985.274
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of presentation of cutaneous melanoma, squamous cell cancer and basal cell cancer in the Oxford Region

Abstract: Summary The seasonality of presentation of 1019 skin melanomas in Oxford Region 1952Region -1975 Several recent studies (Fears et al., 1977;Houghton et al., 1978;Wigle, 1978;Swerdlow, 1979;Houghton et al., 1980;Houghton & Viola, 1981;MacKie & Aitchison, 1982) have suggested that cutaneous malignant melanoma incidence may have a short induction period after exposure to sun radiation. One finding which could be interpreted as supporting this hypothesis is the seasonal pattern of first diagnosis of melanoma foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…Previous studies indicated that MM diagnosis was possibly influenced by seasonal fluctuations [5,6,7,8,9,10,11]. In a global assessment, a bimodal distribution indicated peaks of incidence in late spring/early summer and in autumn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that MM diagnosis was possibly influenced by seasonal fluctuations [5,6,7,8,9,10,11]. In a global assessment, a bimodal distribution indicated peaks of incidence in late spring/early summer and in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…The term chronomics was coined to refer to timing and rhythm influences on cancer biology [2,3,4]. Another different and probably unrelated feature is represented by seasonality in skin cancer detection that has previously been suggested in Westernized populations [5,6,7,8,9,10,11]. In these studies, the diagnosis of cutaneous malignant melanoma (MM) appeared more frequent in late spring/early summer [5,7,8,9,10] and also in autumn [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the monthly incidence of ocular melanoma in other populations have also reported little or no similarity to cutaneous melanoma. Swerdlow found no statistical evidence of seasonality of ocular melanoma incidence among males or females in Oxford, UK, in contrast to a later report on cutaneous melanoma in that region (Swerdlow, 1983(Swerdlow, , 1985. In a study of 238 cases of ocular melanoma reported to the New York State tumour registry between 1975 and 1979 and aggregated into six two-month periods, a peak in the incidence was found in May-June for males and September-October for females (Polednak, 1985).…”
mentioning
confidence: 61%
“…Regarding seasonal variations, higher incidence of female breast cancer has been reported for the spring and summer (Cohen et al, 1983;Mason et al, 1985), and circannual contrasts have also been found for other tumours (Newell et al, 1985;Swerdlow, 1985; Hermida and Ayala, 1996). As for the thyroid, some studies have reported seasonal variations in endocrine parameters, with variables such as T3, T4 and thyroid-stimulating hormone (TSH) being higher in the autumn or winter (Halberg et al, 1981;Nicolau et al, 1987;Haus et al, 1988).…”
mentioning
confidence: 99%